A Translocation Renal Cell Carcinoma with Skeletal Muscle Metastasis in a Child - Gülen TÜYSÜZ; Nihal ÖZDEMİR; Haluk EMİR; Haydar DURAK; Sergülen DERVİŞOĞLU; İbrahim ADALETLİ; Hilmi APAK (Federation of Turkish Pathology Societies, 2017)
Renal cell carcinoma is a tumor that is well known for a high rate of metastasis to several locations like the lung, liver and bones. Skeletal muscle is a rare location for dissemination of the disease. Herein, we describe a 7-year-old boy who presented with flank pain. On physical examination, an abdominal mass located on the left kidney as well as a solid palpable lesion on the left upper arm were detected. Total nephrectomy with subsequent excision of the arm mass was performed. Pathology examination revealed presence of translocation renal cell carcinoma. The patient received α-interferon followed by multikinase inhibitor (Sorafenib) treatment but was lost due to progressive disease. This is the first description of a pediatric patient with skeletal muscle metastases of translocation renal cell carcinoma in the literature.